LEAF CHLOROPHYLL METER- A NON-DESTRUCTIVE METHOD FOR SCHEDULING NITROGEN IN POTATO CROP - singh, shiv pratap (Potato Journal, 2019)
A leaf chlorophyll meter (SPAD 502) was used as a tool for N-fertilization in potato. SPAD value of an overfertilized plot was used as reference to application of subsequent split doses after earthing up in different treatment plotsfor two prevalent varieties Kufri Jyoti and Kufri Chandramukhi. In different treatments the SPAD values differed fortwo varieties. Among different treatments (N schedules) higher SPAD value was observed throughout in over fertilizedreference plots where 125% of recommended N was applied. In tuber yield, Kufri Jyoti (36.7 t/ha) was higher than KufriChandramukhi (30.5 t/ha) at all N levels/treatments. Total tuber yield under different N doses ranged from 33.1(KufriChandramukhi) to 34.8 (Kufri Jyoti) t/ha. Among various N schedules and levels there was no significant difference intuber yield, though, the highest yield was obtained in the treatment where 10% of recommended N was applied at 95%of reference SPAD after basal (50%) and earthing up (20%) applications followed by in over fertilized plot there bysaving 20% of recommended N (36 kg/ha). This indicated that increasing the number of splits of N supplied N to thecrop for longer duration to maintain the yield level of both varieties compared to over fertilized plot even at much lowerN application rate. The best period to detect N deficiency in potato for corrective N fertilization was found to be on orbefore 45 DAP which is tuberization phase. Gross return (2.26 lakh/ha), net return (1.53 lakh/ha) and B:C ratio (3.1) washigher with Kufri Jyoti compared to Kufri Chandramukhi. Among different N treatments gross return (2.09 thousand /ha), net return (1.37 thousand/ha) and B : C (2.9) ratio were highest with 50% at planting + 20% at earthing + 10% at 95%reference value. Thus, there was 20% saving of N by splitting of N based on SPAD value.